2018
DOI: 10.1007/s11011-018-0258-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile of oxidative stress and trace elements in febrile seizures among children

Abstract: Febrile seizures (FS) are frequent convulsive disorders, occurring in infants and young children. The present study aims to assess and compare the serum levels of oxidative stress markers and some essential trace minerals in FS with normal or abnormal EEG and evaluate the effect of antioxidant therapy on the clinical outcome. This study has been carried out on 80 children with FS (40 with simple FS and 40 with complex FS) and 40 febrile children without seizures. Clinical and EEG findings were recorded for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…In our study, epileptic patients with past history of febrile seizures showed significant decrease in zinc serum level in comparison to patients without history of febrile seizures. This agreed with previous studies which revealed low zinc serum level in children with febrile seizures in comparison with controls [37][38][39][40] and in comparison with children who had acute febrile illness without febrile seizures [41]. Several studies support the idea that low zinc levels increase seizure susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, epileptic patients with past history of febrile seizures showed significant decrease in zinc serum level in comparison to patients without history of febrile seizures. This agreed with previous studies which revealed low zinc serum level in children with febrile seizures in comparison with controls [37][38][39][40] and in comparison with children who had acute febrile illness without febrile seizures [41]. Several studies support the idea that low zinc levels increase seizure susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, the hemoglobin and hematocrit levels of the group with recurrent FS was statistically meaningfully lower than rst time FS patients group. Even though there is no linkage found in literature about serum zinc levels and recurrence of FS [29,59], in our study, serum zinc levels of recurrent FS group was statistically signi cantly lower compared to rst time FS patient group. Average serum zinc level was below normal for both groups.…”
Section: Discussioncontrasting
confidence: 79%
“…Disulfide (µmol / l) / alb (g / l). Oxidative stress index = total oxidant status / total antioxidant status) [19][20][21][22][23][24][25][26][27]. The results of hemogram and Vitamin B12, 25 OH D levels were retrospectively taken from their files.…”
Section: Laboratory Analysismentioning
confidence: 99%